Stress-Driven Discovery of Novel Cryptic Antibiotics from a Marine Fungus Penicillium sp. BB1122 - Auckloo, Bibi N.; Pan, Chengqian; Akhter, Najeeb; Wu, Bin; Wu, Xiaodan; He, Shan (Frontiers in Microbiology, 2017)
Standard laboratory cultures have long been known to hinder activation of specific gene clusters which in turn hamper production of secondary metabolites with unique properties due to lack of innovation or the inability to trigger cryptic gene clusters’ expression. Due to challenges related to the avoidance of the isolation of replicated metabolites, resistance-developing pathogens are to be addressed by the scientific community worldwide in order to progress with novel and potent compounds which could further be developed in the future for pharmaceutical usage. This study reports the isolation of novel cryptic antibiotics from a marine fungus Penicillium sp. BB1122 collected from Zhoushan coast by applying the ‘metal-stress’ strategy, here referring to the heavy metal cobalt (6mM). HPLC-guided isolation of four novel and four known compounds belonging to the polyketide class has been carried out where their relative as well as absolute configurations have been determined using spectroscopic analysis techniques as well as by the comparison of theoretically calculated ECD spectrum and the experimental ECD spectrum, respectively. The structures of novel compounds 7 and 8 represent the first example of 2,5-dioxabicyclo[2.2.1]heptane pyrone backbone bearing a migrated polyene chain. The novel compounds 8, 7 and 5 exhibited potent antibiotic properties against S. aureus, B. subtilis and E. coli with MIC values ranging from 0.25 µg/mL to 4 µg/mL. The results showed that cobalt stress is an effective strategy to discover novel antibiotics from microorganisms.